Analisis Peran Guru PAI dalam Meningkatkan Keterampilan Berpikir Kritis Siswa PAI di Sekolah Menengah Atas: Penelitian - Okta Rosfiyani; Ataya Thalita Fawaz; Rizki Fadillah; Aqila Zulfa Ali; Galang Rafli Yus Saputra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Critical thinking skills are essential to face the various challenges that exist in today's world. Therefore, it is expected that Islamic religious education (PAI) teachers can organize learning processes that encourage students to conduct critical analysis, assessment, and reflection on Islamic principles. This study aims to examine the role of PAI teachers in the development of critical thinking skills among high school studentsstudents(SMA). This research used a qualitative approach with a case study method in one of the vocational schools. Data were collected through in-depth interviews with PAI teachers and students, observation of the learning process, and document analysis such as rubrics of students' critical thinking skills, lesson plans and teaching materials. The results showed that PAI teachers acted as facilitators, motivators, and mediators in developing students' critical thinking skills through discussion, case study, and problem-based learning methods. However, challenges such as time constraints, curriculum load, and low student interest in abstract topics are still an obstacle.Overall, this study revealed that the active role of PAI teachers in implementing innovative learning strategies can improve students' critical thinking skills, although school policy support and teacher professional development are needed to optimize the results. The results of this study provide recommendations to educators and decision makers to improve training for teachers and incorporate critical literacy elements into the PAI curriculum.